Sexual violence and sexuality education for the vulnerable sex: evidence from rural south-eastern Nigeria (2019)
Violence against children is one of the violations of human rights. Although studies have been done on sexual violence against female children, there are gaps in understanding of this phenomenon particularly in Nigeria. Conducted in Ngwo, a rural community in Enugu State, South-eastern Nigeria, the study presents evidence on the reality and extent of violence experienced by the girlchild in this setting. Findings revealed that sexual violence in this area and typically goes unreported. It was also found that knowledge of sexuality education was lacking in breadth and depth. Although more studies are needed to associate lack of sexuality education and experiences of sexual violence, the study concludes that female children are highly vulnerable to sexual violence. We suggest that comprehensive sexuality education can be an important factor in curbing sexual violence. Together with increased awareness and advocacy that target parents, teachers and the society at large, governmental intervention with regards to adequate sanction for perpetrators, introduction of structures for reporting sexual violence and rehabilitation of victims of sexual violence are also critical to dealing with this problem.